Development of a Low-Cost Precision Drop Tester Integrating Digital Height Measurement and Rapid Release Mechanism for Academic Packaging Labs - Ralisnawati, Dani; Kurniawan, Muhammad Prasetya; Setioningrum, Desy; Astuti, Ratdiyanti Puji (Jurnal Ilmiah Inovasi, 2025)
Drop testing is a key method in evaluating the mechanical durability of packaging and products during distribution. This research develops a low-cost drop tester prototype that is precise and applicable for academic environments, referring to ASTM D5276 and ISTA standards. The integrative design using CAD/CAE and FEA simulation ensures the mechanical strength and reliability of the structure, while the electronic system based on microcontroller and ultrasonic sensor supports digital drop height measurement and deformation monitoring through high-speed camera. Experimental validation shows an average fall height deviation of less than 1 mm with stable fall orientation and quick release mechanism. Weaknesses such as the absence of arm height limit, limitations of the load cell sensor in recording load peaks, and the need for lubrication and maintenance of the slider are the focus of further development. Recommendations include full automation of data logging and application of AI for video analysis of the test process. This prototype has the potential to improve the quality of practicum learning and open up space for research development and packaging industry applications.